Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) Pada Kurikulum Merdeka di SD Negeri 18 Kota Padang - Annisa Arinil Haq; Dwi Rahayu; Nailul Azmi Denoya; Salsabila Fitrian (Universitas Maritim AMNI Semarang, 2024)
This research aims to find out how the Strengthening Pancasila Student Profile (P5) Project activities at SD Negeri 18 Padang City are implemented and their impact on students. This research uses a qualitative approach with descriptive methods. The instruments used in this research are documentation, interviews and observation. Data was collected through interviews with one of the class V teachers who implemented an independent curriculum in learning, and involved 4 classes starting from grades 3-6 as participants in P5 activities. In this case, implementing the independent curriculum, students are involved in implementing projects as part of these activities. Based on the results of observations of the implementation of P5 at SD Negeri 18 Padang City, it can be concluded that implementing P5 is a very important approach in achieving the Pancasila Student Profile. P5 activities provide students with the opportunity to increase their knowledge, which plays a crucial role in the formation of their character. Moreover, P5 allows students to learn from their surroundings, which enriches their learning experience.